Distal Shoe Space Maintainer for the Premature Loss of Primary Second Molar in a 5-Year-Old Patient: A Case Report - Sarjana Mishra1 , Susant Mohanty2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Uneventful loss of deciduous second molar, afore the eruption of first permanent molar could lead tounadorned malocclusion due to undesired loss of space in the arch, tipping, crowding of the dental archand many other dental problems. So, to avoid further occlusal complications, it is desirable to place a spacemaintainer after successful extraction of the carious primary molar. This case report describes the removalof a primary mandibular second molar, followed by delivery of a distal shoe appliance before the eruptionof the first permanent molar.